Clinical Evaluation of Two Ayurveda Treatment Regimes in Ekakustha (International Journal of Ayurveda and Pharma Research, 2023)
Psoriasis is one of the most dreadful dermatological conditions affecting 3.5% of population of the world and in India prevalence of Psoriasis varies from 0.44% to 2.88%. Males and females are equally predisposed and all age groups are affected. Psoriasis is common genetically determined inflammatory skin disorder of unknown cause which in its most usual form is characterized by well demarcated raised red swelling patch that preferentially localize to extensor surfaces, which is compared to Ekakustha. Acharya particularly emphasized Shodhan Chikitsa in the Kushtha treatment because of its repeated relapse. Shodhan therapy has obvious advantages over Shaman therapy because it overcomes repeated relapses. Twenty patients were selected and randomly divide into two groups with 10 patients in each group. In group A Vaman with Krutvedhan followed by Virechana and Basti was given. In group B Vaman with Madanphala followed by Virechana and Basti was given. Comparing the symptomatic improvement in all two groups it was found that average percentage of relief was slightly higher in Group B (Vaman with Madanphala) in comparison to Group A (Vaman with Krutvedhan). The average reduction of PASI score is more in group B. but statistically the difference between the effects of two therapies is insignificant, so it is concluded that Shodhana Karma gives significant results in subjective and objective parameters of Ekakushtha irrespective of the medicine used in Vamana Karma.